Hepatitis E induced "acute-on-chronic" liver failure - do we transplant or not? : "Acute-on-chronic" zatajenje jetre uzrokovano hepatitis E virusnom infekcijom - transplantirati ili ne? - Dinjar Kujundžić, Petra (Array, 2020)
Hepatitis E virus is a pathogen of worldwide significance. In developed countries, foodborne transmission of zoonotic genotypes is the most common route of infection. Transfusion transmitted infection is also an important source of infection, particularly in immunocompromised population. In most cases, HEV infection is asymptomatic or presents as an acute self-limiting hepatitis. Rarely it leads to fulminant hepatitis or „acute-on- chronic” liver failure in people with pre-existing chronic liver diseases. The aim of this report is to present the first documented case of HEV-related „acute-on-chronic” liver failure in Croatia in a patient with chronic liver disease listed for liver transplantation. Due to increasing incidence in industrialised countries, HEV infection should always be considered in the differential diagnosis of acute hepatitis and in patients with unexplained worsening of chronic liver disease.